EXPLORING RELATIONSHIP BETWEEN LEARNERS’ ROLES AND READING CIRCLE’S TASKS - Jincheng, Zeng; Rahmat, Noor Hanim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study examines the relationship between learners’ roles and tasks in Reading Circles (RCs) within China’s EFL context, where teacher-centred instruction prevails. The quantitative survey analysed 431 Chinese college EFL learners’ perceptions of RC roles and tasks after a semester-long intervention using a 31-item Likert-scale survey. Results showed structured roles (e.g., Summarizer, Discussion Leader) significantly increased engagement (p < .01) and reduced anxiety (d = 0.42), though complex tasks (e.g., Connector) elicited lower confidence. Over 70% endorsed role rotation, but 35% struggled with dense texts, highlighting the need for pre-reading supports. Learners demonstrated greater autonomy and critical thinking skills through collaborative role-based activities, with participation rates increasing by 40% compared to traditional reading instruction. However, cultural factors such as reluctance to express dissenting opinions and preference for teacher validation influenced role effectiveness. Key pedagogical implications include scaffolding roles by proficiency level, integrating metacognitive strategies to enhance reading comprehension, and blending group collaboration with individual accountability tasks to optimize learning outcomes. Future research should explore the implementation of hybrid RC-digital models that incorporate technology-enhanced features and investigate the longitudinal effects of sustained RC practice on learners’ reading proficiency and autonomous learning capabilities in diverse EFL contexts.